COMMUNITY-BASED HEALTH-PROFESSIONS INTERPROFESSIONAL EDUCATION: A COLLABORATIVE AND SUSTAINABLE MODEL - Tri Nur Kristina; Sudaryanto Sudaryanto; Fatikhu Yatuni Asmara; Nuryanto Nuryanto; Firman Wirakusumah; Yoni Syukriani (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2018)
Background: Community health problems should be solved comprehensively dan collaboratively by involving several health professionals. Combination of Community-based education (CBE) with Interprofessional education (IPE) might contribute in the management of community health problems and give experiences of health team collaboration for health professions students.Method: This was a preeliminary study to develop and to validate Model CBE-IPE. Research was done in the Faculty of Medicine Diponegoro University, Semarang involving 3 study programs i.e. Medicine, Nursing, and Nutrition. Research method was qualitative study by using document analyses to develop draft model followed by Focus Group Discussion (FGD) to validate the model. Results: Based on comparability of the curriculum and acquired competencies, the model can only be sufficient if implemented for students in 6th semester. The model has  been agreed to be implemented with several input and suggestions. Small group of students should work together to assess health problems in 1-2 family, to implement intervention, to monitor and evaluate their intervention, and to report their work. Assessment including activity, peer assessment, family evaluation, ability of presentation and discussion, and report writing. Perceptions of students, instructurs, and community member will be asked after implementation to evaluate the program. Conclusion: Model of CBE-IPE suggested to be implemented for students who have sufficient competencies to be applicated in the community. Review and further validation of this model is still needed after implementation.